Testing a cognitive-decisional mediation model through the integration of the cognitive mediation model and the spiral of silence theory - Al-Kandari, Ali A.; Frederick, Edward; Alsaber, Ahmad; AlReshaid, Faisal; Alhashem, Fatimah (Frontiers in Communication, 2025)
IntroductionThis study introduces a Cognitive-Decisional Mediation Model (CDMM) to explain and predict opinion expression as a behavioral outcome. The model posits that individuals’ motives for media use—specifically surveillance gratification-seeking and heterogeneous opinion exposure motives—initiate a process of cognitive engagement that shapes opinion expression.MethodsTwo cross-sectional survey studies were conducted to test the CDMM. Study 1 included 502 respondents, and Study 2 included 826 respondents. The model examines how media-use motives influence cognitive activities—cognitive elaboration, perceived familiarity with an issue, and diversity of retained information—which in turn affect information instrumentality, defined as confidence in using retained information for opinion expression. At the final stage, information instrumentality, fear of social isolation (FS), and opinion congruency were modeled as direct predictors of opinion expression.ResultsFindings from both studies revealed that the surveillance motive path exerted a stronger influence on opinion expression than the heterogeneous opinion exposure motive path. Information instrumentality consistently emerged as a significant predictor of opinion expression. Moreover, the mediating effect of perceived familiarity on information instrumentality was stronger than that of information diversity across both samples.DiscussionThe results support the theoretical validity of the proposed CDMM, highlighting the central role of cognitive mediation and decisional confidence in explaining opinion expression behaviors. The study contributes to the broader field of political communication and behavioral research by clarifying how individuals’ motives and cognitive processes jointly shape their willingness to express opinions in social contexts.